Exploring the Role of Sex and Sexual Experience in Predicting American Indian Adolescent Condom Use Intention Using Protection Motivation Theory - Chambers, Rachel Strom; Rosenstock, Summer; Lee, Angie; Goklish, Novalene; Larzelere, Francene; Tingey, Lauren (Frontiers in Public Health, 2018)
Introduction: American Indian (AI) youth experience poor sexual health outcomes. Research indicates the Protection Motivation Theory (PMT) is a robust model for understanding how sexual risk and protective behaviors are associated with condom use intention (CUI). Studies indicate the constructs of the PMT which influence CUI vary by sex and sexual experience. This analysis explores associations between PMT constructs and CUI by sex and sexual experience among AI youth who participated in the Respecting the Circle of Life (RCL) trial, a sexual and reproductive health intervention. Methods: We analyzed baseline data from the sample of 267 AIs, ages 13–19, who participated in the evaluation. We examined CUI and PMT construct scores by sex and sexual experience utilizing generalized estimated equations and multiple regression models to test which PMT constructs were associated with CUI across sex and sexual experience. Results: Twenty-two percentage of participants were sexually experienced; 56.8% reported CUI at baseline. We found several differences in scores in PMT constructs by sex and sexual experience including self-efficacy, response efficacy, vulnerability, severity, and extrinsic rewards. We also found constructs varied that were associated with CUI varied across sex and sexual experience. No PMT constructs were associated with CUI among sexually experienced youth. Conclusion: Results provide support for developing, selecting and delivering sexual health programs by sex and sexual experience in American Indian communities. Girls programs should focus on internal satisfaction and self-worth while boys should focus on negative impacts of not using condoms. Programs for youth who are not sexually active should focus on negative impacts of not using condoms. Programs for sexually inactive youth should work to change peer norms around condom use and improve knowledge about the efficacy of condom use.